Wacana Desentralisasi: Pengalaman Indonesia dan Cina - Wonoadi, Grace Lestariana (Jurnal Hubungan Internasional, 2012)
This paper tries to make a comparison of decentralization policy which done by Indonesia and China. For big countries, areas which is far from the central government often led to the legitimacy crisis. Decentralization is one of effort to reduce the weight of central government responsibility. With considering the institutions valuation, comparative study of Indonesian and China Government in running decentralization are valued as quite significant.